Knowledge, Attitude, and Practice Regarding Sleep Hygiene Among Medical Students in Bangladesh - Mir Moyeedul Islam; Ummee Aziza Wahid; Sanjoy Saha (Mediscope, 2025)
Background: Sleep hygiene is crucial for both physical and mental health, especially for medical students who deal with demanding coursework and pressures. Psychological issues and poor academic performance are associated with poor sleeping habits. Despite its importance, the knowledge, attitudes, and sleep hygiene habits of Bangladeshi medical students have not yet received sufficient attention. Methods: At Ad-din Sakina Women's Medical College and Hospital in Jashore, 200 medical students were selected by convenience sampling for this cross-sectional survey. A standardized, pre-tested questionnaire covering four areas—demographics, knowledge, attitude, and sleep hygiene practice—was used to collect data. Version 25 of the SPSS software was used to conduct descriptive analysis. Results: Most respondents (78.5%) reported awareness of sleep hygiene, but behavioral practices indicated significant gaps. While 97% cleaned their beds before sleep and 79% prayed before bed, 90% used social media at night, and only 6% avoided caffeine before bedtime. Nearly half (44.5%) reported insufficient sleep, and 42% experienced persistent anxiety. Though 98% recognized insomnia as a public health issue, fewer acknowledged the risks of sleeping pill dependency (49%) and addiction (31.5%). Conclusion: The findings highlight a disparity between knowledge and behavior concerning sleep hygiene. Although awareness is relatively high, unhealthy practices persist. There is a critical need for structured educational interventions focusing on behavioral change and sleep literacy. These efforts could enhance well-being and academic performance among medical students and future healthcare providers. Mediscope 2025;12(2): 79-83